Bronze Age Cultures in Central and Eastern Europe - Gimbutas, Marija (1965)
espec. 32-35: Commercial relations between eastern central Europe and the Near East in EB ca. 1800-1650 B.C.; 65-69: Mycenaean influences in the northern Pontic area and the commercial relations between the Black Sea, the Caucasus, and the Near East in EB ca. 1650-1450 B.C.; 88-94: Commercial relations between the Aegean and the northern Pontic area, the Caucasus, and the Near Bast in MB ca. 1450-1250 B.C.